Chiral separation by enantioselective liquid-liquid extraction - Schuur, Boelo; Verkuijl, Bastiaan J V; Minnaard, Adriaan J; de Vries, Johannes G; Heeres, Hero J; Feringa, Ben L (Organic & biomolecular chemistry, 2011)
The literature on enantioselective liquid-liquid extraction (ELLE) spans more than half a century of research. Nonetheless, a comprehensive overview has not appeared during the past few decades. Enantioselective liquid-liquid extraction is a technology of interest for a wide range of chemists and chemical engineers in the fields of fine chemicals, pharmaceuticals, agrochemicals, fragrances and foods. In this review the principles and advances of resolution through enantioselective liquid-liquid extraction are discussed, starting with an introduction on the principles of enantioselective liquid-liquid extraction including host-guest chemistry, extraction and phase transfer mechanisms, and multistage liquid-liquid extraction processing. Then the literature on enantioselective liquid-liquid extraction systems is reviewed, structured on extractant classes. The following extractant classes are considered: crown ether based extractants, metal complexes and metalloids, extractants based on tartrates, and a final section with all other types of chiral extractants.